2015
DOI: 10.1159/000368498
|View full text |Cite
|
Sign up to set email alerts
|

Association of Visceral Fat Area with Chronic Kidney Disease and Metabolic Syndrome Risk in the General Population: Analysis Using Multi-Frequency Bioimpedance

Abstract: Background/Aims: Advances in bioimpedance analysis (BIA) technologies now enable visceral fat area (VFA) to be assessed using this method. The aim of this study was to evaluate the clinical relevance and usefulness of VFA as a predictor of chronic kidney disease (CKD) and metabolic syndrome (MS), using BIA. Methods: We identified 24,791 adults who underwent voluntary routine health checkups at Yeungnam University Hospital. In total 22,480 patients were recruited into our study. Participants were divided into 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 35 publications
0
35
1
3
Order By: Relevance
“…Adiponectin was not measured in this study, but low adiponectin and visceral fat area has previously been shown to be highly intercorrelated [16]. Thus, our findings do not exclude the possibility of an interaction in subgroups, and SUA and adiponectin may act synergistically with regard to more advanced stages of CKD [58][59][60], and in subjects with less favourable values of SUA, adiponectin and the urinary biomarkers. This matter is of relevance since pharmaceutical agents such as PPAR γ agonists [21,22] and some blockers of the renin-angiotensin system [61,62] are known to simultaneously decrease SUA and increase adiponectin, and thus these biomarkers may share common pathways.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Adiponectin was not measured in this study, but low adiponectin and visceral fat area has previously been shown to be highly intercorrelated [16]. Thus, our findings do not exclude the possibility of an interaction in subgroups, and SUA and adiponectin may act synergistically with regard to more advanced stages of CKD [58][59][60], and in subjects with less favourable values of SUA, adiponectin and the urinary biomarkers. This matter is of relevance since pharmaceutical agents such as PPAR γ agonists [21,22] and some blockers of the renin-angiotensin system [61,62] are known to simultaneously decrease SUA and increase adiponectin, and thus these biomarkers may share common pathways.…”
Section: Discussioncontrasting
confidence: 59%
“…Therefore, extrapolation of the results to patients with more extreme values should not be done. In a recently published, large cohort study it was demonstrated that visceral fat area, assessed by multi-frequency bioimpedance , as well as with SUA [58]. Adiponectin was not measured in this study, but low adiponectin and visceral fat area has previously been shown to be highly intercorrelated [16].…”
Section: Discussionmentioning
confidence: 58%
“…More importantly, we have shown that change in body composition parameters (ovehydration and lean tissue mass) were significantly correlated with the degree of frailty as measured by the Frailty Score (Table 2). A previous study also reported that visceral fat content, as measured by bioimpedance analysis, is a simple method for predicting the risk of chronic kidney disease and metabolic syndrome in the general population [23]. Since the primary objective of our study was to determine the prevalence and contributing factors of frailty, we did not perform extensive analysis on the possible clinical implications of central obesity in PD patients, which has been examined in detail in another study by our group [24].…”
Section: Discussionmentioning
confidence: 99%
“…По данным Kang S. H., et al (2015) [32], увеличение площади вис-церального жира (по данным оценки методом биоимпе-данса) в популяции 22 480 пациентов старше 18 лет сопровождается увеличением частоты встречаемости хронической болезни почек (ХБП) с 6,9 % до 13,9 % и 25,2 % (р < 0,001) по мере увеличения содержания жировой ткани (низкое, среднее и высокое соответ-ственно). Проведенный анализ продемонстрировал воз-можность использования оценки процентного содержа-ния жировой ткани в качестве раннего предиктора фор-мирования ХБП (62,66 % (95 % CI, 61,0-64,3) и 64,22 % (95 % CI, 63,5-64,9).…”
Section: выпуск 1 (61) 2017unclassified